Evaluating Alliance Bioversity & CIAT’s role in transforming National Food Systems in Vietnam (2023- 2030) - Perez, Salomon; Rivera, Tatiana; Gonzalez, Carolina; Buritica, Alexander; Urbani, Ilaria (2024)
This impact brief, the second of the Impact Brief Series by the Performance, Innovation, and Strategic Analysis for Impact program of the Alliance of Bioversity International and CIAT, evaluates the role of the Alliance in transforming Vietnam's food systems. The study examines how the Alliance, in collaboration with key institutions, supported the development of Vietnam's National Action Plan (NAP) for food systems and its potential impacts. Outcome Trajectory was used to identify and analyze achieved outcomes, tracing the various influences leading to these changes. Word Cloud Analysis was employed for visually summarize feedback from interviews, utilizing statistical software to create visual diagrams of word relationships and patterns.